RENEB intercomparisons applying the conventional Dicentric Chromosome Assay (DCA). (2nd January 2017) - Oestreicher, Ursula; Samaga, Daniel; Ainsbury, Elizabeth; Antunes, Ana Catarina; Baeyens, Ans; Barrios, Leonardo; Beinke, Christina; Beukes, Philip; Blakely, William F.; Cucu, Alexandra; De Amicis, Andrea; Depuydt, Julie; et al.
Abstract: Purpose: Two quality controlled inter-laboratory exercises were organized within the EU project 'Realizing the European Network of Biodosimetry (RENEB)' to further optimize the dicentric chromosome assay (DCA) and to identify needs for training and harmonization activities within the RENEB network. Materials and methods: The general study design included blood shipment, sample processing, analysis of chromosome aberrations and radiation dose assessment. After manual scoring of dicentric chromosomes in different cell numbers dose estimations and corresponding 95% confidence intervals were submitted by the participants. Results: The shipment of blood samples to the partners in the European Community (EU) were performed successfully. Outside the EU unacceptable delays occurred. The results of the dose estimation demonstrate a very successful classification of the blood samples in medically relevant groups. In comparison to the 1st exercise the 2nd intercomparison showed an improvement in the accuracy of dose estimations especially for the high dose point. Conclusions: In case of a large-scale radiological incident, the pooling of ressources by networks can enhance the rapid classification of individuals in medically relevant treatment groups based on the DCA. The performance of the RENEB network as a whole has clearly benefited from harmonization processes and specific training activities for the network partners.